Morphological Structure of Upland Rice Varieties at Different Light Intensities - Khairunnisa Khairunnisa (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2022)
Increasing food self-sufficiency, especially rice grown as intercrops, requires attention to the development ofupland rice varieties that are shade-tolerant and capable of high production. The objective of this research tostudy about the mechanism of tolerance, morphological characters as characterizing tolerance to shade. Theresearch was carried out in Cengkeh Turi Binjai with an altitude of ± 32 meters above sea level, with soil pH;4.5, started from May to August 2018. The study used a split plot design with two factors. The first factorwas the light intensity, consist of: 100%, 75%, 50%, and 25%. The second factor consisted of 5 rice varieties,namely: Inpago 5, Lipigo 4, Inpago 8, Inpago 10, and Lipigo 2. The result of this study was an increase in thearea of the flag leaf with a decrease in sunlight intensity by 75%. The conclusion of this study is that thelower the intensity of sunlight, the lower the angle of the flag leaf and the thickness of the upland rice leaf.Keywords: light; upland rice; varieties